The Influence of Bali Brand Equity on Tourists Traveling Behavior - Surya Diarta, I Ketut (E-Journal of Tourism, 2015)
There is already known that brand equity of tourism destination can influence tourist decision making to choose a destination to be visited. However, there is no information on how tourism destination brand equity influences tourist’s behavior during their vacation in destination such as extend tourist length of stay, encourage to be revisit tourist, and willing to recommend for others. This research aims to analyze the effect of Bali brand equity on tourists traveling behavior. The research was conducted from January to November 2015 in five main tourism objects in Bali. Data were collected through survey of 240 foreign tourists and analyzed using multivariate analysis of variance (MANOVA). The research result shows that the influence of Bali brand equity to tourists traveling behavior  as a whole through destination brand awareness,  destination brand image, destination brand association, and destinastion perceived quality. While, individually: (a) the frequency of visiting Bali is affected by distinctive features for stunning natural beauty of Bali and safe and peaceful Bali turism destination, (b)  the length of stay during vacation in Bali is affected Bali as one of the world's main destination, strong brand Bali recall, warm-politely-friendly local people, safe and peaceful destination, and excellent tourism physical facilities, and (c) the frequency recommending Bali to others is affected by distinctive features for stunning natural beauty of Bali, warm-politely-friendly local people, and safe and peaceful destination. Give stressing on the attributes of destination that develop tourist’s positive behavior to Bali as a tourism destination will determine the success of Bali in world tourism market competition.
Keywords: destination, brand, equity, Bali, behavior